Studi Kritis Bahan Ajar Sejarah Kebudayaan Islam Kelas XI di MAN 1 Kota Sukabumi: Analisis Diskoneksi Metodologis dan Rekonstruksi Instruksional - Siti Sarifah; Siti Qomariyah; Eni Nurainillah; Siti Zainab; Aang Purnawirawan (Jurnal Pendidikan, Bahasa dan Budaya, 2026)
This study aims to critically examine the Islamic Religious Education (PAI) teaching materials on the topic of "The History of the Emergence of the Abbasid Caliphate" within the Islamic Cultural History (SKI) course for Class XI at MAN 1 Kota Sukabumi. This comprehensive analysis evaluates key educational elements: learning objectives, instructional materials, methods, media, and evaluation instruments. Employing a descriptive qualitative research design, data were collected through observation, unstructured interviews, and systematic documentation. Data analysis was executed using content analysis, covering data reduction, data presentation, and conclusion drawing, validated through source and technique triangulation. The research findings reveal a severe methodological disconnection in the existing teaching materials: (1) learning objectives are heavily dominated by low-level cognitive domains (LOTS); (2) the material structure lacks a clear demarcation between facts, concepts, and principles; (3) critical thinking methods are absent from authentic problem-solving situations; (4) planned media remain overly generic, relying on non-credible internet resources (ilmuguru.org); and (5) evaluation instruments suffer from cognitive reductionism due to the absence of specific grids, indicators, and scoring rubrics. In conclusion, a total instructional reconstruction is urgent to achieve constructive alignment. This is proposed through the integration of the Problem-Based Learning (PBL) model, the utilization of specific visual-spasial media (geographical maps of underground movements and genealogical charts), and the implementation of authentic assessments oriented toward Higher Order Thinking Skills (HOTS).